Women's Leadership Styles: Indonesian Context - K.A RAHMAN; FIRMAN FIRMAN; YUSDI ANDRA; SAMSUDIN SAMSUDIN; YULITA YULITA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aimed to explore and describe the leadership styles of a female principal in one state senior high school in Indonesia, as well as how the perceptions of the school members about her leadership style. This study used qualitative method with a case study approach. The participants were six people, including the principal, vice principal (student affairs), vice principal (curriculum), head of administration, student council president and security guard. Interview data were analyzed using